Europäisches Nordmeer, Ostküste von Island bis Norwegen / Herausgegeben vom Oberkommando der Kriegsmarine 1910 - Germany. Kriegsmarine. Oberkommando; (Berlin : Oberkommando der Kriegsmarine;, 1939)
Kleine Berichtigungen: . 1939 Relief shown by spot heights. Depths shown by soundings and isolines.; Includes chart coverage key, inset map of Jan Mayen (scale 1:200,000) and abbreviation table.; "Nr. 157."; Selected lights hand colored in yellow Color; 1:1,200,000